Literasi Kesehatan Digital dan Kapasitas Sumber Daya Manusia dalam Layanan Kesehatan Primer Indonesia: Scoping Review - Meiliza Izzatika; Rizma Adlia Syakurah; Najmah Najmah (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
The rapid advancement of digital health technologies has transformed the delivery of primary health care (PHC) globally. Digital Health Literacy (DHL) has become a critical competency for PHC workers, particularly in Indonesia, alongside the implementation of SATUSEHAT and the Six Pillars of Health Transformation, which depend on the digital capacity of the health workforce. This scoping review aims to synthesize evidence on: (1) the role of DHL in strengthening PHC workforce capacity; (2) system-level benefits of investing in DHL; (3) barriers to its development; and (4) evidence-based policy recommendations for Indonesia and comparable LMICs. The review followed the Arksey & O’Malley (2005) framework, with searches conducted in PubMed/MEDLINE, Scopus, Frontiers, and WHO repositories. Keywords included digital health/eHealth literacy, primary health care, health workers, and capacity building, while grey literature from the Indonesian Ministry of Health and ASEAN health authorities was also included. Screening and data extraction were conducted independently by two reviewers. DHL improves clinical decision-making, health information management, patient engagement, interprofessional collaboration, and continuous professional development. At the system level, it enhances service quality, efficiency, equity, and health surveillance. Key barriers include limited infrastructure, low baseline DHL, unequal access to training, data privacy concerns, and fragmented training approaches. Five policy recommendations were proposed. Strengthening DHL requires a multi-level strategy integrating training, digital infrastructure support, ethical regulatory frameworks, and a national action plan. Investment in DHL is a fundamental requirement for achieving universal health coverage in Indonesia.